‘Loaded’: indie guitar rock, canonism, white masculinities - Bannister, Matthew (Popular Music, 2006)
Indie alternative rock in the 1980s is often presented as authentically autonomous, produced in local scenes, uncaptured by ideology, free of commercial pressures, but also of high culture elitism. In claiming that the music is avant-garde, postmodern and subversive, such accounts simplify indie's historical, social and cultural context. Indie did not simply arise organically out of developing postpunk music networks, but was shaped by media, and was not just collective, but also stratified, hierarchical and traditional. Canon (articulated through practices of archivalism and connoisseurship) is a key means of stratification within indie scenes, produced by and serving particular social and cultural needs for dominant social groups (journalists, scenemakers, tastemakers, etc.). These groups and individuals were mainly masculine, and thus gender in indie scenes is an important means for deconstructing the discourse of indie independence. I suggest re-envisioning indie as a history of record collectors, emphasising the importance of rock ‘tradition’, of male rock ‘intellectuals’, second-hand record shops, and of an alternative canon as a form of pedagogy. I also consider such activities as models of rational organisation and points of symbolic identification.